The resilience of nurses in the emergency department of Sanglah Hospital during the pandemic of COVID-19 in Bali, Indonesia - Kumalasari, Heni; Lubis, Dinar Saurmauli; Kurniati, Desak Putu Yuli (Public Health and Preventive Medicine Archive, 2024)
Background and purpose: COVID-19 pandemic has a major impact on the health care system, including nurses. The rapid increase in the number of patients, lack of knowledge of the disease, and the high risk of being exposed to the virus, are some challenges faced by nurses in hospitals. During this situation, nurses need to build resilience to provide good services for patients as well as to protect themselves from COVID-19 infection. This study aims to explore resilience of the emergency room (ER) nurses at Sanglah Hospital Denpasar during the early stage of COVID-19 pandemic. Methods: A qualitative study with a phenomenological approach was conducted in the ER of Sanglah Hospital Denpasar, from October to November 2020. Data were collected through in-depth interviews that involved six nurses. The information collected include nurses' experiences in dealing with pandemics, nurses' knowledge about COVID-19, challenges and obstacles to nursing services during the COVID-19 outbreak, efforts to protect themselves, family and closest relatives, as well as management responses regarding the protection of health workers, especially among nurses. Data were analyzed by Interpretive Phenomenological Analysis (IPA) and presented narratively. Results: Nurses have the internal strength to deal with increased workloads and working conditions that were considered difficult during the pandemic situation. Nurses’ resilience is also formed by external supports such as from co-working partners, family, and organizations. The challenges and obstacles faced in maintaining resilience are the implementation of services, amidst the uncertainty of the status of COVID-19 patients and the stigma among health workers, as they were suspected as virus carriers. Efforts to strengthen resilience are conducted by increasing capacity, taking care of oneself, and setting work schedules. Conclusion: The resilience of nurses consists of the resilience to face increased workloads and difficult working conditions during a pandemic. This resilience comes from internal and external strengths such as friends and organizations. In difficult situations, nurses are still able to think of concrete steps to protect themselves and their families. However, challenges and obstacles need to be overcome to improve the quality of patient care during a pandemic.